2011
DOI: 10.1088/0004-6256/142/4/129
|View full text |Cite
|
Sign up to set email alerts
|

THE CLUSTER POPULATION OF THE IRREGULAR GALAXY NGC 4449 AS SEEN BY THEHUBBLEADVANCED CAMERA FOR SURVEYS

Abstract: We present a study of the star cluster population in the starburst irregular galaxy NGC 4449 based on B, V, I, and Hα images taken with the Advanced Camera for Surveys on the Hubble Space Telescope. We derive the cluster properties such as size, ellipticity, and total magnitudes. Cluster ages and masses are derived fitting the observed spectral energy distributions with different population synthesis models. Our analysis is strongly affected by the age-metallicity degeneracy; however, if we assume a metallicit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 87 publications
5
61
0
Order By: Relevance
“…In fact, regardless of the details of the triggering mechanism, the occurrence of a starburst in an Irr should necessarily i) create a central concentration of mass and increase the central surface brightness; and might possibly ii) form a central nucleus by the inspiralling and merging of star clusters (Gnedin et al 2013), which are often found in BCDs (e.g., Annibali et al 2009Annibali et al , 2011. In particular, the nuclei of Sphs are generally bluer than the overall stellar body (e.g., Lotz et al 2004), suggesting that they contain younger stellar populations than the rest of the galaxy.…”
Section: The Link Between Bcds and Rotating Sphsmentioning
confidence: 99%
“…In fact, regardless of the details of the triggering mechanism, the occurrence of a starburst in an Irr should necessarily i) create a central concentration of mass and increase the central surface brightness; and might possibly ii) form a central nucleus by the inspiralling and merging of star clusters (Gnedin et al 2013), which are often found in BCDs (e.g., Annibali et al 2009Annibali et al , 2011. In particular, the nuclei of Sphs are generally bluer than the overall stellar body (e.g., Lotz et al 2004), suggesting that they contain younger stellar populations than the rest of the galaxy.…”
Section: The Link Between Bcds and Rotating Sphsmentioning
confidence: 99%
“…Throughout the literature, there is consensus and evidence that both the initial cluster mass and luminosity functions (CMF and CLF, respectively) are well described by a power-law slope of approximately −2 (Whitmore et al 1999;Larsen 2002;Bik et al 2003;Gieles et al 2006;Mora et al 2009;Whitmore et al 2010;Chandar et al 2014;Whitmore et al 2014, among many others). It has also been observed that the range for the recovered CLF slopes in several nearby galaxies is quite large, d -< < -2.8 1.5 (e.g., Adamo et al 2011;Annibali et al 2011;Whitmore et al 2014). Blending effects, important in crowded fields and in galaxies at large distances (above 80 Mpc), have the tendency to flatten the slope of the CLF (Randriamanakoto et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This fraction is observed to increase as function of the SFR of the galaxy, suggesting that the fraction of star formation happening in clusters (hereafter Γ or cluster formation efficiency, CFE) is increasing . Indeed direct evidence of a varying CFE as function of the average galactic star formation rate density (ΣSFR) has been observed in numerous galaxies (e.g., Goddard et al 2010;Adamo et al 2011;Annibali et al 2011;Ryon et al 2014, among many others).…”
Section: Introductionmentioning
confidence: 99%